On the Content of the Concept of a Material Breach of Law as the Grounds for the Cancellation or Change of a Court Decisionin Cassation Proceeding - Vasilii S. Zhelonkin (Сибирское юридическое обозрение, 2017)
The article analyses special aspects in the concept of a material breach of law. The difference is shown between referring to a material breach as a base to cancel or modify a judgment, applied by a legislator in accordance with part 1, article 401/15 and reference stated in part 1, article 389.17 of the Criminal Procedure Code of the Russian Federation. It is proved that a material breach of law can be admitted as a base to cancel or modify judgment by Appeal Court only in case it effects the legality of a Lower-level Court judgment.